Flavonoids and Their Role As Anti-Inflammatory Agents - Fatmawati; Aliah Ramadhani Puteri; Humairah Binti Huda (Biomedical Journal of Indonesia, 2024)
The human civilizations have been using plants and herbs for their rich sources of phytonutrients and bioactive compounds. Polyphenols are one of the groups of beneficial compounds found naturally, they include a wide variety of molecules and are divided into 4 main categories, which are flavonoids, phenolic acids, lignans, and stilbenes. It is estimated that more than 10,000 flavonoid compounds have been isolated and then identified, with the results finding that the majority of flavonoids are widely accepted as therapeutic agents. It is found in various flowers, fruits, and leaves such as red peppers, celery, parsley, chamomile, mint, and ginkgo biloba. Flavonoids are known for their anti-inflammatory properties using a mechanism that is thought to be different. The mechanism used may include an enzyme inhibition mechanism for enzymes that regulate transcription factors. This has a very important role, one of the roles being the control of mediators involved in an inflammatory process. The study for this systematic review was conducted without a time constraint using scientific databases such as Google Scholar and ScienceDirect, with 5 years’ time limitation. Previous research has validated the pharmacological characteristics of some flavonoids and their potential health advantages.